Expanding the genetic architecture and phenotypic spectrum in the skeletal ciliopathies. - Zhang, Wenjuan; Taylor, S Paige; Ennis, Hayley A; Forlenza, Kimberly N; Duran, Ivan; Li, Bing; Sanchez, Jorge A Ortiz; Nevarez, Lisette; Nickerson, Deborah A; Bamshad, Michael; Lachman, Ralph S; Krakow, Deborah; et al. (Hum Mutat, 2018)
Defects in the biosynthesis and/or function of primary cilia cause a spectrum of disorders collectively referred to as ciliopathies. A subset of these disorders is distinguished by profound abnormalities of the skeleton that include a long narrow chest with markedly short ribs, extremely short limbs, and polydactyly. These include the perinatal lethal short-rib polydactyly syndromes (SRPS) and the less severe asphyxiating thoracic dystrophy (ATD), Ellis-van Creveld (EVC) syndrome, and cranioectodermal dysplasia (CED) phenotypes. To identify new genes and define the spectrum of mutations in the skeletal ciliopathies, we analyzed 152 unrelated families with SRPS, ATD, and EVC. Causal variants were discovered in 14 genes in 120 families, including one newly associated gene and two genes previously associated with other ciliopathies. These three genes encode components of three different ciliary complexes; FUZ, which encodes a planar cell polarity complex molecule; TRAF3IP1, which encodes an anterograde ciliary transport protein; and LBR, which encodes a nuclear membrane protein with sterol reductase activity. The results established the molecular basis of SRPS type IV, in which mutations were identified in four different ciliary genes. The data provide systematic insight regarding the genotypes associated with a large cohort of these genetically heterogeneous phenotypes and identified new ciliary components required for normal skeletal development.
Keywords: Ciliopathies; Cytoplasmic Dyneins; Genetic Association Studies; Genetic Markers; Genetic Variation; Genotype; Humans; Mutation; Phenotype; Proteins; Radiography; Skeleton; Whole Exome Sequencing

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis. - Zieba, Jennifer; Zhang, Wenjuan; Chong, Jessica X; Forlenza, Kimberly N; Martin, Jorge H; Heard, Kelly; Grange, Dorothy K; Butler, Merlin G; Kleefstra, Tjitske; Lachman, Ralph S; Nickerson, Deborah; Regnier, Michael; et al. (Sci Rep, 2017)
Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form of the disease due to heterozygosity for missense or nonsense mutations in MYH3, which encodes embryonic myosin. Cells transfected with the MYH3 missense mutations had reduced TGFβ signaling, revealing a regulatory role for embryonic myosin in the TGFβ signaling pathway. In wild-type mice, there was persistent postnatal expression of embryonic myosin in the small muscles joining the neural arches of the spine suggesting that loss of myosin function in these muscles contribute to the disease. Our findings demonstrate that dominant mutations in MYH3 underlie autosomal dominant SCT, identify a postnatal role for embryonic myosin and suggest that altered regulation of signal transduction in the muscles within the spine may lead to the development of vertebral fusions.
Keywords: Abnormalities, Multiple; Alleles; Bone Morphogenetic Proteins; Cytoskeletal Proteins; Female; Genes, Dominant; Genotype; Humans; Lumbar Vertebrae; Male; Musculoskeletal Diseases; Mutation; Myosins; Phenotype; Radiography; Scoliosis; Signal Transduction; Synostosis; Thoracic Vertebrae; Transforming Growth Factor beta; Whole Exome Sequencing

Destabilization of the IFT-B cilia core complex due to mutations in IFT81 causes a Spectrum of Short-Rib Polydactyly Syndrome. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Forlenza, Kimberly N; Spiro, Rhonda P; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Sci Rep, 2016)
Short-rib polydactyly syndromes (SRPS) and Asphyxiating thoracic dystrophy (ATD) or Jeune Syndrome are recessively inherited skeletal ciliopathies characterized by profound skeletal abnormalities and are frequently associated with polydactyly and multiorgan system involvement. SRPS are produced by mutations in genes that participate in the formation and function of primary cilia and usually result from disruption of retrograde intraflagellar (IFT) transport of the cilium. Herein we describe a new spectrum of SRPS caused by mutations in the gene IFT81, a key component of the IFT-B complex essential for anterograde transport. In mutant chondrocytes, the mutations led to low levels of IFT81 and mutant cells produced elongated cilia, had altered hedgehog signaling, had increased post-translation modification of tubulin, and showed evidence of destabilization of additional anterograde transport complex components. These findings demonstrate the importance of IFT81 in the skeleton, its role in the anterograde transport complex, and expand the number of loci associated with SRPS.

An inactivating mutation in intestinal cell kinase, ICK, impairs hedgehog signalling and causes short rib-polydactyly syndrome. - Paige Taylor, S; Kunova Bosakova, Michaela; Varecha, Miroslav; Balek, Lukas; Barta, Tomas; Trantirek, Lukas; Jelinkova, Iva; Duran, Ivan; Vesela, Iva; Forlenza, Kimberly N; Martin, Jorge H; Hampl, Ales; et al. (Hum Mol Genet, 2016)
The short rib polydactyly syndromes (SRPS) are a group of recessively inherited, perinatal-lethal skeletal disorders primarily characterized by short ribs, shortened long bones, varying types of polydactyly and concomitant visceral abnormalities. Mutations in several genes affecting cilia function cause SRPS, revealing a role for cilia function in skeletal development. To identify additional SRPS genes and discover novel ciliary molecules required for normal skeletogenesis, we performed exome sequencing in a cohort of patients and identified homozygosity for a missense mutation, p.E80K, in Intestinal Cell Kinase, ICK, in one SRPS family. The p.E80K mutation abolished serine/threonine kinase activity, resulting in altered ICK subcellular and ciliary localization, increased cilia length, aberrant cartilage growth plate structure, defective Hedgehog and altered ERK signalling. These data identify ICK as an SRPS-associated gene and reveal that abnormalities in signalling pathways contribute to defective skeletogenesis.
Keywords: Abnormalities, Multiple; Cilia; Exome; Female; Hedgehog Proteins; Humans; Infant; MAP Kinase Signaling System; Pedigree; Pregnancy; Protein-Serine-Threonine Kinases; Sequence Analysis, DNA; Short Rib-Polydactyly Syndrome; Signal Transduction; Skeleton